Flavobacterium meningosepticum Meningitis: Report of Selected Aspects - Rios, Israel (1978)
Two patients developed meningitis due to Flavobacterium meningosepticum. Because of resistance to most available antimicrobial agents, intravenous and intraventricular erythromycin was administered to one patient. Subsequent development of resistance to erythromycin prompted the use of intravenous and intraventricular rifamycin, which eventually resulted in cure. Diagnosis of F. meningosepticum meningitis in the second patient was delayed, and appropriate therapy was not administered until 4 days prior to the patient's death. Of 82 previously published cases, only 4 occurred in adults. Therapy of meningitis due to this organism has been a difficult problem, and we suggest possible modes of therapy, based on our experience and a review of the literature.